2017
DOI: 10.1038/s41598-017-05036-2
|View full text |Cite
|
Sign up to set email alerts
|

A New Paradigm for Understanding and Enhancing the Critical Heat Flux (CHF) Limit

Abstract: Nearly a century of research on enhancing critical heat flux (CHF) has focused on altering the boiling surface properties such as its nucleation site density, wettability, wickability and heat transfer area. But, a mechanism to manipulate dynamics of the vapor and liquid interactions above the boiling surface as a means of enhancing CHF has not been proposed. Here, a new approach is implemented to limit the vapor phase lateral expansion over the heat transfer surface and actively control the surface wetted are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
(48 reference statements)
5
19
0
Order By: Relevance
“…Due to the near-kinetic-limit condition, PCHT at the transition show high heat flux achieved at small superheat. Figure 5 shows the heat flux vs. HTC plot of the transition points measured in this work for various fluids (stars in Figure 2 achieved for experiments with water, which is close to the previously reported record-high CHF in boiling heat transfer by Moghaddam et al [17]. In this work, what is perhaps more remarkable is for the other three fluids with lower surface tension, which showed that the heat fluxes and HTC at the transition points are significantly higher than those from the traditional pool boiling or evaporation.…”
Section: Near Kinetic Limit At the Onset Of Pore-level Thin Film Evapsupporting
confidence: 88%
See 1 more Smart Citation
“…Due to the near-kinetic-limit condition, PCHT at the transition show high heat flux achieved at small superheat. Figure 5 shows the heat flux vs. HTC plot of the transition points measured in this work for various fluids (stars in Figure 2 achieved for experiments with water, which is close to the previously reported record-high CHF in boiling heat transfer by Moghaddam et al [17]. In this work, what is perhaps more remarkable is for the other three fluids with lower surface tension, which showed that the heat fluxes and HTC at the transition points are significantly higher than those from the traditional pool boiling or evaporation.…”
Section: Near Kinetic Limit At the Onset Of Pore-level Thin Film Evapsupporting
confidence: 88%
“…Extensive efforts have been made to enhance the CHF and decrease the wall superheat using various strategies, including managing the bubble nucleation sites [5][6][7], increasing the surface wettability/capillarity using micro/nanostructures (which usually also increases the nucleation site density and provides a fin effect with an enhanced heat transfer area) [8,9], increasing the contact line length [10,11], providing separate liquid-vapor pathways for enhanced macroconvection [12,13], preventing bubble coalescence by pinning the contact line [14], and combination of multiple mechanisms stated above. Significant CHF enhancement has been demonstrated up to ~400 W cm -2 [15], but the CHF is still relatively low compared with flow boiling and other new configurations using water [16,17]. Moreover, the CHF of pool boiling for nonaqueous fluids is usually significantly lower than that of water due to the difference in the thermophysical properties, such as the latent heat of vaporization.…”
Section: Introductionmentioning
confidence: 99%
“…(E) A superhydrophobic vapor permeable membrane pulls the bubbles away from the heated surface. 232 slow due to the depleted superheat at the liquid-vapor interface. Very recently, a thin film boiling phenomena was reported on a nanoporous membrane structure to reduce the liquid layer thickness and thus accelerating bubble growth and departure (Figure 11D).…”
Section: =16mentioning
confidence: 99%
“…In contrast to the existing studies that focused on the structural surface design, a superhydrophobic vaporpermeable membrane was recently put several hundred micrometers away from the heated hydrophilic surface to efficiently remove the bubbles at a smaller size (Figure 11E). 232 Compared with the bubble removal driven by the buoyancy on the heated surfaces, the growing bubbles can be pulled away from the heated surface by the additional surface tension when the growing bubbles contact with the superhydrophobic membrane. The rapid removal of the bubbles can greatly reduce the bubble departure size and limit the vapor phase lateral expansion over the heated surface, which enables an ultrahigh CHF of 1.8 kW/cm 2 .…”
Section: =16mentioning
confidence: 99%
See 1 more Smart Citation